Catalysts Deactivation, Poisoning and Regeneration - Lisi, Luciana (MDPI - Multidisciplinary Digital Publishing Institute, 2019)
Catalyst lifetime represents one of the most crucial economic aspects in industrial catalytic processes, due to costly shutdowns, catalyst replacements, and proper disposal of spent materials. Not surprisingly, there is considerable motivation to understand and treat catalyst deactivation, poisoning, and regeneration, which causes this research topic to continue to grow. The complexity of catalyst poisoning obviously increases along with the increasing use of biomass/waste-derived/residual feedstocks and with requirements for cleaner and novel sustainable processes. This book collects 15 research papers providing insights into several scientific and technical aspects of catalyst poisoning and deactivation, proposing more tolerant catalyst formulations, and exploring possible regeneration strategies.